Who Can See My Stuff? Online Self-Disclosure and Gender Differences on Facebook - Farinosi, Manuela and Taipale, Sakari (Observatorio (OBS*), 2018)
This study investigates the gendered privacy practices and concerns on Facebook, by leaning on the idea of privacy management as a form of digital labour. We analyse if young Facebook users are more concerned about the privacy against other users than against Facebook as a company or against third-party partners. We also analyse if privacy concerns and visibility rules are differentiated by gender. Using a structured online survey, we collected responses from a sample of 813 Italian university students (aged 18-34). Our results show that the respondents have just slightly more privacy concerns against other users than against Facebook, and much less against third-party partners. Unlike a majority of previous studies, we show that women are consistently more concerned about privacy-related risks than men, which can be associated with efforts to take care of digital labour in their everyday life.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTU4NDcvb2Jzb2JzMTIxMjAxODExMjk